Alfred Lvovich Shmelkin (12.06.1938 — 22.12.2015) (Algebra and Discrete Mathematics, 2016)
With deep sorrow and regret we learnt about the death on December 22, 2015 of our colleague, Alfred Lvovich Shmelkin, a prominent algebraist, Honoured Professor of Lomonosov Moscow State University and member of ADM editorial board over the past thirteen years.